Sex determination in Northern Thai from crania by using computer-aided design software and conventional caliper methods - Toonlanat Thuanthong (2020)
© 2018 Toonlanat Thuanthong, Paiwan Sudwan, published by Sciendo. Identification of sex from skeletal remains is an essential step in forensic anthropology. The skull is the second choice, after the pelvis, to estimate sex by osteometric methods. To evaluate the process of identification of sex in Northern Thai from crania by using computer-aided design (AutoCAD) software and conventional caliper methods. Dry skulls of 86 men and 74 women were examined. AutoCAD software and digital calipers were used to measure dimensions. Eleven of the 15 parameters were created for this study. Men are significantly larger than women in all parameters, except in the nasospinale-prosthion measurement. There were no significant differences in the intraobserver error test and between the AutoCAD and digital caliper measurements. The logistic regression analysis yielded a sex classification accuracy rate of 92.9% in men, 93.4% in women, and 93.1% of overall accuracy for AutoCAD software. When using digital calipers, there was an accuracy rate of 89.3% in men, 94.7% in women, and 91.9% for overall accuracy. AutoCAD software is a reliable method to predict the sex and provide high accuracy in sex determination from crania.